2016
DOI: 10.1016/j.jdent.2016.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water-aging on self-healing dental composite containing microcapsules

Abstract: Objectives The objectives of this study were to develop a self-healing dental composite containing poly(urea-formaldehyde) (PUF) shells with triethylene glycol dimethacrylate (TEGDMA) and N,N-dihydroxyethyl-p-toluidine (DHEPT) as healing liquid, and to investigate the mechanical properties of the composite and its self-healing efficacy after water-aging for 6 months. Methods PUF microspheres were synthesized encapsulating a TEGDMA-DHEPT healing liquid. Composite containing 30% of a resin matrix and 70% of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 59 publications
0
34
0
1
Order By: Relevance
“…Efficient self-healing has been also demonstrated in previous studies using the applied method of fabrication of microcapsules [ 29 , 31 ]. The microencapsulated healing is quite stable and durable, which broadens the process window for fabricating self-healing composites and prevents the deterioration of the healing capability of the composites during storage [ 32 ]. The successful demonstration of this healing system will open pathways for healing in dental composites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient self-healing has been also demonstrated in previous studies using the applied method of fabrication of microcapsules [ 29 , 31 ]. The microencapsulated healing is quite stable and durable, which broadens the process window for fabricating self-healing composites and prevents the deterioration of the healing capability of the composites during storage [ 32 ]. The successful demonstration of this healing system will open pathways for healing in dental composites.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of protein adsorbed on the composite discs was determined by the micro bicinchoninic acid method [ 32 ]. Six disks were evaluated for each group.…”
Section: Methodsmentioning
confidence: 99%
“…Reports on the use of poly(urea formaldehyde) microcapsules (average diameter: 70 µm) filled with TEGDMA and a tertiary amine (N,N-dihydroxyethyl-p-toluidine, DHEPT) as activator in experimental composites were recently published. 60,61,62 This self-repair system uses benzoyl peroxide (BPO) added to the resin matrix as initiator to polymerize the healing liquid. In the first study, 62 these microcapsules were added to a BisGMA-TEGDMA resin.…”
Section: Strategy 2a: Fiber-reinforced Compositesmentioning
confidence: 99%
“…61 Healing efficiency of composites with 7.5% of TEGDMA-DHEPT microcapsules was not affected by prolonged water storage of the specimen prior to initial K 1c test (up to six months), or when healing took place in water. 60 A self-healing dental composite (or, more precisely, a compomer) based on glass ionomer cement chemistry was recently developed. 52 Silanated silica microcapsules filled with an aqueous solution of polyacrylic acids (average diameter: 29 µm) were prepared and dispersed in an experimental composite containing a photocurable BisGMA/HEMA matrix and 70 wt% of strontium fluoroaluminasilicate glass particles.…”
Section: Strategy 2a: Fiber-reinforced Compositesmentioning
confidence: 99%
“…Once cracking occurs, its propagation ruptures the shells and finally the healing materials flow as a result of capillary action to seal the crack. In this context, Wu et al [11] employed urea-formaldehyde to encapsulate N,N-Dihydroxyethyl-p-toluidine (DHEPT) and triethylene glycol dimethacrylate (TEGDMA) for developing a self-healing dental composite. It was found that the incorporation of 7.5% healing microcapsules results in only 64%-70% recovery.…”
Section: Introductionmentioning
confidence: 99%